Tinjauan Kualitas Data Klinis Pasien Bedah Pada Rekam Medis Rawat Inap Di RS BHAYANGKARA TK. III HOEGENG IMAM SANTOSO BANJARMASIN - Apit Widiarta; Safril Safril; Rizki Puspita; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2016)
Surgery patient’s clinical data at inpatient medical record in Bhayangkara Tk. III Hoegeng Imam Santoso Banjarmasin Hospital is illegible especially at operation report and course of disease physician instruction form. Moreover, also found incompleteness of clinical data especially at discharge summary.The qualified clinical data consist by seven criteria, is legible, reliable, precise, complete, consistent, clear, and timely.The purpose of this research is to find the surgery patient’s clinical data quality on inpatient medical record. This research is descriptive research, use saturated sampling technique with surgery patient’s inpatient medical record as the population and 79 surgery patient’s inpatient medical record, with data collection methods observation, documentation study, and interview, use univariate analysis and presented in tabular and textural.The result from 79 surgery patient’s inpatient medical record shows the percentage of patient’s clinical data quality is 73,61% (good) consist legibility85,4% (very good), reliability 100% (very good), precise 100% (very good), completeness 67,5% (good), consistency 17,7% (very less), clear 89,87% (very good) and timely 89,7% (adequate).